2022
DOI: 10.1093/jole/lzad003
|View full text |Cite|
|
Sign up to set email alerts
|

The scientometric landscape of Evolang: A comprehensive database of the Evolang conference

Abstract: Language evolution is a modern incarnation of a long intellectual tradition that addresses the fundamental question of how language began. Such a formulation is intuitively obvious, but a more precise characterisation of this area of research with its central notions—language and evolution—has proved surprisingly elusive. In this paper, we show how conceptual analysis can be complemented with scientometric analysis in describing language evolution. To this end, we built a database containing information on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…But the term iterated learning has also come to refer to an approach that operationalizes this fundamental process of generational transmission via computer simulations or in the laboratory. Iterated learning is an approach that has proven particularly successful in language evolution researchin fact, scientometric analyses of abstracts from the pertinent conferences in the field have shown that it is among the most central topics in the field (e.g., Bergmann & Dale 2016;Wacewicz et al 2023b). The IL model was pioneered in Kirby's (2001) seminal computational simulation.…”
Section: Iterated Learning: Computational Approaches and Behavioural ...mentioning
confidence: 99%
See 1 more Smart Citation
“…But the term iterated learning has also come to refer to an approach that operationalizes this fundamental process of generational transmission via computer simulations or in the laboratory. Iterated learning is an approach that has proven particularly successful in language evolution researchin fact, scientometric analyses of abstracts from the pertinent conferences in the field have shown that it is among the most central topics in the field (e.g., Bergmann & Dale 2016;Wacewicz et al 2023b). The IL model was pioneered in Kirby's (2001) seminal computational simulation.…”
Section: Iterated Learning: Computational Approaches and Behavioural ...mentioning
confidence: 99%
“…While questions from the domain of historical linguistics have long been seen as outside the scope of language evolution research, recent developments in the field suggest that their importance for understanding cultural evolution is acknowledged to an increasing extent. This is shown, for example, by the growing number of presentations for this domain at the most important conferences in the field (see, e.g., Gong et al 2014: 508;Wacewicz et al 2023b). Importantly, the relationship between language evolution research and historical linguistics can be seen as a bilateral one: on the one hand, insights from historical linguistics can prove relevant for language evolution research in that they reveal general processes of cultural evolution; on the other hand, accounts of language change make use of evolutionary concepts to account for historical processes (e.g., Croft 2000; see also Harder 2010).…”
Section: Evolutionary Perspectives On Language Variation and Changementioning
confidence: 99%